Destination Satisfaction and Revisit Intention: Insights From A Systematic Literature Review Of Tourism Research - Abdilla, Mohammad; Wardi, Yunia; Abror, Abror (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
Maintaining tourists' intention to revisit is essential for managing sustainable tourism. Attracting tourists to revisit will require less effort than attracting new visitors and will reduce marketing expenditure because there is no need to build awareness, which can promote sustainable tourism. Previous research has highlighted the significant effect of satisfaction in driving revisit intention. Numerous studies have been conducted on revisit intention and satisfaction, as well as destination satisfaction. Using the Scopus database from 2015 to 2024, these studies were systematically analyzed using PRISMA and the VOSViewer bibliometric analysis tool. The findings of this study will enhance a more comprehensive understanding of literature related to destination satisfaction and revisit intention by identifying themes, research trends, leading journals and publishers in the field, and the relationships between different topics. Results show that satisfaction with various aspects of tourist destinations, such as accommodation quality, tourist attractions, information, political stability, and tourist experiences, plays an essential role in generating tourist loyalty and motivating them to return. This study discovered that destination satisfaction can be affected by several factors, such as destination personality, travel service quality, self-congruity, social media, travel experience and destination image